Effect of age and sex on Obesity Average of Population Sample in Baghdad City (Journal of the College of Basic Education, 2022)
Obesity is a condition characterized by an excess of body fats. Obese persons differ in the amount of excess fat that stores and the regional distribution of that fat within the body. It is therefore essential to distinguish between those at risk as a result of abdominal obesity than those with generalized obesity. There are many studies about the obesity rate in Asia but these studies did not give a clear idea about it in the Asian subgroups, the present research aims to study: 1) obesity rate in another ethnic and cultural Asian subgroups , in Iraq, it depend on gender and age of the groups using different ways such as Body mass index (BMI) and percentage of total body fat (TBF), 2) studies which one way is better to give a realty average of obesity, and 3) diseases risk depend on gender and age of the groups using waist/hip ratio (W/H ratio). this study included 780 individuals. The age of the group was in the range of 6-60 years of both genders with apparently healthy status. The individuals were distributed to different age groups; (6-12 years) including primary school students, (13-19) years including secondary school students, (18-23 years) including undergraduate university students, and (≥24 years) including university employees. BMI, TBF, and W/H ratio were measured in all individuals as WHO reported. This study found that 1) the general frequencies of obesity status according BMI did not exceed (7.8%) from total number of subjects (5.7% in female and 2.1% in male) most of them were ≥24 years old, while it found that obese percentage increased to (44.7%) from total number of subjects according TBF (39% in females and 8% in males) most of them were ≥24 years old. 2) the high risk rate was higher in female compared to males. This risk is elevated with the age, the highest high risk was recorded in ≥24 years group which reached 66% (54.5% in females and only 11.5% in males). In conclusion, such high risk ratio related with the obesity rate according TBF is not reassuring especially for ≥24 year’s group and needs serious stand by, re-measured again larger than the current samples and gives a solution for this problem.